COVID-19: A methyl-group assault?. (April 2021) - McCaddon, Andrew; Regland, Björn
Abstract: The socio-economic implications of COVID-19 are devastating. Considerable morbidity is attributed to 'long-COVID' – an increasingly recognized complication of infection. Its diverse symptoms are reminiscent of vitamin B12 deficiency, a condition in which methylation status is compromised. We suggest why SARS-CoV-2 infection likely leads to increased methyl-group requirements and other disturbances of one-carbon metabolism. We propose these might explain the varied symptoms of long-COVID. Our suggested mechanism might also apply to similar conditions such as myalgic encephalomyelitis/chronic fatigue syndrome. The hypothesis is evaluable by detailed determination of vitamin B12  and folate status, including serum formate as well as homocysteine and methylmalonic acid, and correlation with viral and host RNA methylation and symptomatology. If confirmed, methyl-group support should prove beneficial in such individuals.